Pemanfaatan Mikroalga Dari Limbah Cair Kelapa Sawit Menjadi Bioetanol Dengan Variasi Konsentrasi Asam Sulfat - Diana Aprila; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Combustion of fossil fuels is the main cause of global warming. The high dependence of fuel resource will influence the depletion of fossil resource (oil, natural gas, and coal). Therefore, it is important to develop alternative energy source continuously and environmentally friendly such as bioethanol. Green microalgae like Chlorella purenoidosa has a carbohydrate content in the cellulose and hemicellulose form in its cell wall which can be utilized for bioethanol production. In this research was conducted the conversion of microalgae Chlorella pyrenoidosa to bioethanol as renewable energy. This research aimed to study the effect of acid concentration and temperature on hydrolysis of microalgae and the effect of fermentation time to bioethanol from microalgae hydrolisate. Hydrolysis process conducted for 75 minutes with sulphuric acid concentration 1%, 2%, 3% and 4% (v/v) at 100 oC. The glucose produced was analyzed with Nelson-Somogyi method. Hydrolysis condition that produces highest glucose yield was used to make a substrate for fermentation. Fermentation process conducted for 3 days. Measurement of bioethanol concentration using refractometer. The result showed the highest glucose concentration obtained was 3.51 mg/ml and this was achieved when the hydrolysis occurred at 1% (v/v) sulphuric acid concentration. Fermentation time 3 days provide bioethanol concentration about 0,24875%.Keywords: Chlorella pyrenoidosa, hydrolysis, fermentation, bioethanol.